Advanced non-small-cell lung cancer with epidermal growth factor receptor mutations: current evidence and future perspectives. Issue 10 (October 2013) - Costanzo, Raffaele; Montanino, Agnese; Di Maio, Massimo; Piccirillo, Maria Carmela; Sandomenico, Claudia; Giordano, Pasqualina; Daniele, Gennaro; Franco, Renato; Perrone, Francesco; Rocco, Gaetano; Normanno, Nicola; Morabito, Alessandro
The identification of activating mutations in the tyrosine kinase domain of the EGF receptor (EGFR) predictive of response to tyrosine kinase inhibitors (TKIs) led to a therapeutic revolution in the treatment of patients with metastatic non-small-cell lung cancer (NSCLC). To date, eight randomized clinical trials have demonstrated that first-line treatment with TKIs in advanced NSCLC patients harboring activating EGFR mutations is associated with significant improvement in response rate, progression-free survival, quality of life and tolerability, compared with platinum-based chemotherapy. These results prompted the EGFR TKIs as the current standard first-line treatment of patients with advanced NSCLC harboring activating EGFR mutations. However, there are several questions that need to be addressed, including the best choice among different EGFR TKIs, the treatment of resistant disease and of patients with specific clinical conditions. Ongoing and future, well-designed trials should answer all these questions.